Comparative Effects of Motor and Cognitive Dual- Task Gait Training on balance and mobility in persons with Intellectual Disabilities - Maira Asghar, Sara Aabroo, Sumbal Salik, Sana Manzoor, Shaista Rani, Sania Maqbool, Maria Address, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Dual tasks fall into two main groups: motor dual tasks, which require performance of a motor task and a postural control task at the same time; and cognition dual task that require performance of a cognition task and postural control task at the same time. Aim: To focus on comparative effects of motor and cognitive dual-task gait training on balance and mobility in persons with intellectual disabilities Methodology: A randomized clinical trial was conducted on 52 subjects (n=26) in a District Headquarter Hospital, Mirpur AJK. Fifty-two patients were randomly allocated in two groups as Group A received motor dual task and Group B received cognitive dual task training. Total duration of study was three weeks and assessment done before treatment and after every week. Rancho Los Amigos Cognitive Functional Scale (RLACF), Berg Balance Scale (BBS), Walking While Talking Test (WWT) and Stair Climb Test (SCT) for the assessment of the patient’s improvement in skills, balance and mobility. Results: The results of the study concluded that Rancho Los Amigos Cognitive Function Scale, Berg Balance Scale, Walking While Talking Test and Stair Climb Test scores were improved in both groups significantly. But on comparison; Cognitive dual task training significantly produce better results in improving the balance and mobility in the person with intellectual disability as compared to Motor dual task training with p value<0.005. Conclusion: The study concluded that Cognitive dual task training is statistically and clinically more significant in improving the balance and mobility in the intellectual disable persons as compared to Motor dual task training. Key words: Cognitive dual task, Intellectual disabilities, Motor and cognitive dual-task gait training.